2020
DOI: 10.1186/s12913-020-05410-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of healthcare providers’ confidence in their clinical skills to deliver quality obstetric and newborn care in Uganda and Zambia

Abstract: Background Poor quality obstetric and newborn care persists in sub-Saharan Africa and weak provider competence is an important contributor. To be competent, providers need to be both knowledgeable and confident in their ability to perform necessary clinical actions. Confidence or self-efficacy has not been extensively studied but may be related to individuals’ knowledge, ability to practice their skills, and other modifiable factors. In this study, we investigated how knowledge and scope of practice are associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
2
13
1
Order By: Relevance
“…Information on providers’ demographics and characteristics of facilities were also collected. Results from the two other instruments—knowledge test and confidence assessment—have been published elsewhere [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Information on providers’ demographics and characteristics of facilities were also collected. Results from the two other instruments—knowledge test and confidence assessment—have been published elsewhere [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, nearly all nurses felt confident or somewhat confident in assessment and management of skills across all ABCDE domains. A study in Uganda and Zambia showed that healthcare providers’ confidence increased with exposure to a variety of skills, which will be important to consider when designing the content of a PCC master’s program [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was not a surprising finding as the only ventilators are located at PICU at MJC and in the main ICU at QECH, therefore very few nurses provide care for ventilated patients. Additionally, intubation is not a skill that nurses are permitted to perform or gain competency in and so less familiarity with the procedure may impact confidence in managing related equipment such as endotracheal tubes and ventilators [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, intubation is not a skill that nurses are permitted to perform or gain competency in and so less familiarity with the procedure may impact con dence in managing related equipment such as endotracheal tubes and ventilators. [21] Infrequent exposure may have also impacted nurses' low con dence in ECG interpretation despite nearly 90% con dence with cardiac assessments, as there is no dedicated paediatric cardiac unit and continuous ECG monitoring is not available on most of the paediatric units. Children with cardiac problems receive the same monitoring that other children receive: oxygen saturation, pulse rate, and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Uganda and Zambia showed that healthcare providers' con dence increased with exposure to a variety of skills, which will be important to consider when designing the content of a PCC master's program. [21] Nurses rated high con dence particularly in task-oriented or scale-dependent skills, including the Glasgow or Blantyre Coma Scale, blood glucose monitoring, nasogastric tube management, pain assessment, temperature monitoring, skin assessment, and infection prevention. Further investigation may be revealing as to whether nurses know how to interpret the data they collect, what intervention is indicated based on the ndings, and when to reassess the patient, which would better demonstrate critical thinking skills and a higher level of nursing competency.…”
Section: Discussionmentioning
confidence: 99%